2021
DOI: 10.1044/2020_lshss-20-00025
|View full text |Cite
|
Sign up to set email alerts
|

Print Knowledge in Children With Autism Spectrum Disorder: Do Child and Family Variables Play a Role?

Abstract: Purpose This study aimed to examine the print knowledge of children with autism spectrum disorder (ASD) in comparison to children who have developmental language disorder (DLD) and typically developing (TD) children as well as examine the child and family predictors of print knowledge. Method A total of 629 preschool children, including 33 children with ASD, 93 children with DLD, and 503 TD children, were the focus of the current study. Teachers complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…However, in contrast to our findings, some studies have reported a positive effect of maternal education level on their children's literacy readiness skills (Hofslundsengen, Gustafsson, & Eriksen-Hagtvet, 2019;Hooper et al, 2010). For instance, Dynia and Solari (2021) found that children with autism, whose mothers had higher education levels, exhibited better print awareness, word awareness, and name-writing skills. However, in the case of the Kilis city province examined in the present study, no significant correlation was found between both print awareness and writing readiness scores and maternal education.…”
Section: Correlational Analysescontrasting
confidence: 99%
“…However, in contrast to our findings, some studies have reported a positive effect of maternal education level on their children's literacy readiness skills (Hofslundsengen, Gustafsson, & Eriksen-Hagtvet, 2019;Hooper et al, 2010). For instance, Dynia and Solari (2021) found that children with autism, whose mothers had higher education levels, exhibited better print awareness, word awareness, and name-writing skills. However, in the case of the Kilis city province examined in the present study, no significant correlation was found between both print awareness and writing readiness scores and maternal education.…”
Section: Correlational Analysescontrasting
confidence: 99%
“…Emerging research comparing young children with ASD to their typically developing (TD) peers suggests that there are significant between-group differences in the development of early literacy skills, with children with ASD performing worse than their TD peers (e.g. Dynia et al, 2019;Dynia & Solari, 2021;Smith Gabig, 2010). Evidence also suggests that children with ASD, like TD children, demonstrate heterogenous profiles of development in their early literacy skills (Davidson & Weismer, 2014;Nation et al, 2006).The Simple View of Reading (SVR; Gough & Tunmer, 1986) is often utilized to conceptualize the development of reading.…”
mentioning
confidence: 99%